Exploring EFL Students’ Speaking Anxiety: An Analysis of Levels, Causal Factors, and Coping Mechanisms - Husniah S; Nurdin Noni; Muhammad Tahir (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study investigates the level, sources, and coping mechanisms of speaking anxiety among EFL learners at SMP Negeri 1 Mare. Using a mixed-method design, data were collected through the Foreign Language Classroom Anxiety Scale (FLCAS), semi-structured interviews, and classroom observation. The findings reveal that most students experienced moderate anxiety (42%), followed by high anxiety (30%), indicating that speaking remains a challenging skill for many learners. Three major factors contributing to anxiety were identified: communicative apprehension, fear of negative evaluation, and test anxiety, which frequently manifested in hesitation, avoidance, and physical tension. In response to these challenges, learners employed several coping strategies, including preparation, relaxation, positive thinking, and peer seeking, with preparation being the most frequently used. The study highlights the importance of providing supportive speaking activities and reducing evaluative pressure to help students manage anxiety and improve oral performance. These findings offer valuable implications for EFL teachers in designing anxiety-responsive instructional practices.